Clinical Importance of Mean Corpuscular Volume as a Prognostic Marker After Esophagectomy for Esophageal Cancer: A Retrospective Study. Issue 3 (March 2020) - Yoshida, Naoya; Kosumi, Keisuke; Tokunaga, Ryuma; Baba, Yoshifumi; Nagai, Yohei; Miyamoto, Yuji; Iwagami, Shiro; Iwatsuki, Masaaki; Hiyoshi, Yukiharu; Ishimoto, Takatsugu; Eto, Kojiro; Imamura, Yu; et al.
Abstract : Objective: To elucidate the clinical value of mean corpuscular volume (MCV) for prognostic prediction in patients with esophageal cancer who underwent radical esophagectomy. Background: High MCV is suggested to be relevant to the incidence and prognosis of several malignancies. However, few studies investigating the correlation between MCV and survival outcome of esophageal cancer have been conducted. Methods: This study included 570 patients with esophageal cancer who underwent radical esophagectomy between April, 2005 and December, 2017. Patients were divided into 2 groups according to the standard value of pretreatment MCV: normal (83–99 fL) and high (>99 fL) groups. Clinical backgrounds, short-term outcomes, and prognostic outcomes postesophagectomy were retrospectively compared between the groups. Results: Of all patients, 410 (71.9%) had normal MCV, and 160 (28.1%) had high MCV. High MCV was significantly associated with lower body mass index, higher frequency of habitual alcohol and tobacco use, and higher incidence of multiple primary malignancies other than esophageal cancer. High MCV also correlated with higher incidence of postoperative morbidity of the Clavien–Dindo classification ≥II and pulmonary morbidity. Overall survival was significantly worse in patients with high MCV. Multivariate analysis suggested that high MCV was an independent risk factor for worse survival outcome (hazard ratio 1.54, 95% confidence interval 1.098–2.151, P = 0.012). Conclusions: Patients with high MCV have various disadvantages in clinical background that can adversely affect both short-term and long-term outcomes after esophagectomy. MCV can become a predictive marker to estimate survival outcome after esophagectomy for esophageal cancer. Abstract : Supplemental Digital Content is available in the text